Cluster of nucleons as elementary modes of excitation in nuclei - Dussel, G. G; Liotta, R. J.; Perazzo, R. P. J. (North-Holland Publishing Company, 1982)
Fil: Dussel, G. G Comisión Nacional de Energía Atómica; Argentina